123I-FP-CIT-SPECT in Encephalitis Involving Substantia Nigra. (October 2016) - Tissot, Hubert; Frismand, Solene; Marie, Pierre-Yves; Gospodaru, Nicolaie; Verger, Antoine
Abstract : Abstract: 123 I-FP-CIT-SPECT is currently used to detect functional impairment of striatal structures. We report herein a case where 123 I-FP-CIT abnormalities are seemingly related to an encephalitis involving substantia nigra. A few months after a documented encephalitis, a 19-year-old woman experienced a Parkinsonism with a right dominance. There was a reduction in the striatal binding of 123 I-FP-CIT, especially on the left side, in accordance with the right dominance of the Parkinsonism.